Risk factors for preeclampsia in women - Sánchez Calderón, Sixto (2015)
OBJECTIVE: To identify risk factors for preeclampsia in Peruvían women. Design: Prospective case control clinical study. SETTING: Materno Perinatal Institute and Dos de Mayo Hospital between August 1997 and January 1998. MATERIAL AND METHODS: One hundred eighty-seven preeclampsic women were compared with 193 normotensive pregnant women. Cases were matched to controls regarding Inaternal age and gestational age. Potential associated factors were analyzed using univariated analysis and then logistic regression to adjust to confounders. RESULTS: Pre eclampsia was associated to primiparity but only by univaried analysis (OR. 1,86, IC95: 1,2-3,0). History of a previous pregnancy complicated with preeclampsia was the main risk factor associated to preeclampsia (OR: 9,7. IC95%: 3,4-27,3). Obesity was marginally associated to preeclampsia (OR: 2,1. IC95%: 0,8-5,4) and there was a marginally significative lineartrend (p = 0, 056) for preeclampsia risk as BMI increases. CONCLUSIÓN: Preeclampsia is correlated to several risk factors. Pregnant women who present risk factors found in this and other studies should be controlled carefully in order to reduce the incidence and complications of this hypertensive disorder.